The Sunna and Shi'a in history division and ecumenism in the Muslim Middle East - Bengio, Ofra; Litvak, Meir (Palgrave Macmillan, 2011)
Sunni-Shi'i relations have undergone significant transformations in recent decades. In order to understand these developments, the contributors to the present volume demonstrate the complexity of Sunni-Shi'i relations by analyzing political, ideological, and social encounters between the two communities from early Islamic history to the present